Gestational exposure to antidepressants and risk of seizure in offspring: A systematic review and meta-analysis. (December 2021) - Leung, Miriam T.Y.; Wong, Kirstie H.; Ho, Phoebe W.H.; Ip, Patrick; Wei, Li; Wong, Ian C.K.; Man, Kenneth K.C.
Highlights: The use of antidepressants in pregnant women is a complex decision. Antidepressants use during pregnancy and the risk of seizure in neonates is unclear. Our meta-analysis confirmed the association between antidepressants and seizure in neonates. However, our result did not support causality. Abstract: In spite of the preliminary evidence suggesting a link between gestational use of antidepressant and neurodevelopmental disorders in their offspring, the association between maternal use of antidepressants during pregnancy and the risk of neurologically-related adverse outcomes such as neonatal seizure is still unclear. This study summarises the available evidence on the association between gestational exposure to any antidepressants and the risk of seizure in neonates and children. We found that gestational antidepressant exposure is associated with a 2.3-fold higher incidence of seizure in offspring. Although a causal relationship cannot be confirmed in view of other potential confounders, our findings warrant future research on related clinical aspects, and possibly more careful monitoring of foetal neurodevelopment in pregnant women taking antidepressants during pregnancy. However, this does not suggest the abrupt withdrawal of antidepressants during pregnancy for all cases at risk of seizure in offspring as this must be balanced with the risk of negative consequences caused by untreated maternal depression, and decision-making should be individualised for each patient.